Free-Radical Scavenging Activity (FRSA) of Secondary Metabolite Extracted from Indonesian Eucheuma spinosum - Inayah, Nurul; Masruri, Masruri (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2021)
IIndonesia is the biggest country in the production of red seaweed of Eucheuma spinosum. The red seaweed has bioactive compounds that have a potential activity such as phenolic compounds as well as carrageenan and pigments. This paper reported phytochemical analysis of E. spinosum harvested by a local farmer in Sumenep Island, East Java and free-radical scavenging activity (FRSA) derived from 2,2â€™-diphenyl-1-picrylhdrazyl (DPPH) for several organic solvents. For extraction, dried powder is added with 5.0 mL of various solvents following by ultra-sonication assisted extraction for 30 minutes. The extract was separated by centrifugation for phytochemical analysis and radical scavenging evaluation. The prospecting of dichloromethane, ethyl acetate, and n-hexane extracts indicated the potency for radical scavengers. Alkaloids, terpenoids, and saponins were secondary metabolites that indicated the presence in the extracts. The best IC50 value was presented by ethyl acetate extracts (384,86 ppm) with 38.78% for 50 ppm, while IC50 values of n-hexane, methanolic, dicloromethane extracts were 410.12, 677.76 and 685.08 ppm, respectively.Â Keywords: Eucheuma spinosum, phytochemical analysis, radical scavenging activity